2016
DOI: 10.1111/hepr.12796
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the albumin–bilirubin grade in patients with hepatocellular carcinoma: Validation in a Chinese cohort

Abstract: The ALBI grade, which was featured by simplicity and objectivity, gained a superior prognostic value than that of C-P grade in patients with hepatocellular carcinoma who underwent liver resection. Future well-designed studies with larger sample sizes are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 36 publications
(71 reference statements)
2
43
1
Order By: Relevance
“…Apart from long‐term survival, the ALBI grade has also been associated with perioperative outcomes . A recent analysis of the National Surgical Quality Improvement Program database from our own group revealed that ALBI grade 2/3 was associated with higher odds of posthepatectomy liver failure (PHLF; OR = 1.57, 95% CI, 1.08‐2.27), bile leak (OR = 1.35; 95% CI, 1.02‐1.80), perioperative transfusion (OR = 2.08; 95% CI, 1.69‐2.55), and 30‐day mortality (OR = 2.40; 95% CI, 1.25‐4.60) following liver surgery for benign and malignant diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from long‐term survival, the ALBI grade has also been associated with perioperative outcomes . A recent analysis of the National Surgical Quality Improvement Program database from our own group revealed that ALBI grade 2/3 was associated with higher odds of posthepatectomy liver failure (PHLF; OR = 1.57, 95% CI, 1.08‐2.27), bile leak (OR = 1.35; 95% CI, 1.02‐1.80), perioperative transfusion (OR = 2.08; 95% CI, 1.69‐2.55), and 30‐day mortality (OR = 2.40; 95% CI, 1.25‐4.60) following liver surgery for benign and malignant diseases .…”
Section: Discussionmentioning
confidence: 99%
“…The ALBI score was established by a training cohort of 1313 Japanese patients with HCC. Some reports were published that the ALBI score was superior for distinguishing patients with better hepatic function . The ALBI score is a simple liver function assessment score because it requires only two parameters, serum albumin and bilirubin, which means that the prognosis could be predicted in any institute or for any modality such as surgery, transarterial chemoembolization, and radiofrequency ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the modified JIS score is the sum of points for two variables of liver damage grade classification and the Japanese TNM classification . The ALBI score is a simple and objective measure of liver function and is applicable to HCC at all stages of chronic liver disease unlike the Child–Pugh score that is conventionally restricted to patients with cirrhosis . It is based on serum bilirubin and albumin and was derived from, and subsequently validated by, rigorous statistical analysis of over 6000 patients with HCC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations